Dinamika Relasi Mertua-Menantu dalam Mengupayakan Keharmonisan Keluarga Besar Kristen - Meitha Sartika (Sekolah Tinggi Teologi Sumatera Utara, 2025)
A harmonious relationship within the extended family, particularly between mothers-in-law and daughters-in-law, is a common challenge in Christian marriages within the Indonesian cultural context. This study aims to examine the theological foundation of family harmony and to identify key factors that shape in-law relationships. A qualitative method was employed through literature review, interviews with five participants aged 60–72 who have grandchildren as mother in-law, and with five participants aged 30-40 as daughter in-law. The data were analyzed thematically and compared with biblical principles. The findings reveal that harmony within the extended family aligns with God's will and should be pursued through healthy communication, appropriate role distribution, and mutually agreed boundaries. The relationship between mothers-in-law and daughters-in-law can be nurtured through empathy, acceptance, and the example of faith. Common sources of conflict include competition for attention, economic dependence, and a lack of independence within the nuclear family. These findings offer practical insights for Christian families in fostering extended family relationships that are in accordance with biblical teachings. AbstrakRelasi harmonis dengan keluarga besar, khususnya antara ibu mertua dan menantu perempuan, kerap menjadi tantangan dalam pernikahan Kristen di Indonesia. Penelitian ini bertujuan untuk mengkaji dasar teologis keharmonisan keluarga besar dan menyingkap faktor-faktor yang memengaruhi relasi mertua–menantu. Metode kualitatif digunakan melalui pendekatan studi literatur serta wawancara dengan lima orang narasumber berusia 60–72 tahun sebagai mertua, dan lima orang narasumber berusia 30-40 tahun sebagai menantu. Data dianalisis dengan pendekatan tematik dan dibandingkan dengan prinsip-prinsip Alkitab. Hasil penelitian menunjukkan bahwa keharmonisan keluarga besar adalah bagian dari kehendak Allah yang harus diupayakan melalui komunikasi yang sehat, pembagian peran yang tepat, dan penerapan batasan yang disepakati bersama. Relasi ibu mertua dan menantu perempuan dapat dibangun melalui empati, penerimaan, dan keteladanan iman, sementara konflik umumnya dipicu oleh perebutan perhatian, ketergantungan ekonomi, dan kurangnya kemandirian dalam keluarga inti. Temuan ini memberikan kontribusi praktis bagi keluarga Kristen dalam membina relasi keluarga besar yang selaras dengan prinsip Firman Tuhan.